Pengaruh Digitalisasi Terhadap Efektivitas Administrasi (Studi Kasus Pada Dinas Pendidikan Kota Palembang Bagian Staff Umum dan Kepegawaian) - Ismail, M. Rizki; Saputra, Tedy Setiawan; Sari, Ayu Sumarti; Wulandari, Sri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the impact of digitalization on administrative effectiveness in the Department of Education of Palembang City, particularly in the General and Staffing divisions. Digitalization is a key solution to overcoming bureaucratic barriers, streamlining workflows, and enhancing administrative transparency. This research employs a descriptive quantitative method involving 50 respondents to identify the relationship between digitalization and administrative effectiveness. The findings reveal that digitalization significantly contributes to improving work efficiency by reducing data processing time by up to 50% and minimizing human errors. It also strengthens interdepartmental collaboration through a centralized information system that enables real-time data access. Challenges include limited technological skills, resistance to change, and insufficient infrastructure. Solutions include intensive staff training, infrastructure development, and effective change management strategies. This study supports digital transformation in the government sector to create more efficient public services.